(untitled) (Experimental biology, 2015)
The specialization and features fruiting on plants - owners S. oudemansii Sacc is investigated for the first time. Thus was of interest to find out, whether the specialization macroconidium of a stage S. oudemansii Sacc from microconidium of a stage differs.